‘Valuable Lives to Save’ vs. ‘Babysitting These People While They Try to Kill Themselves’: Changing Police Attitudes Towards Safe Consumption Sites - McNeilly, Rebekah (The British journal of criminology, 2024)
North American police responses to the ‘drug issue’ have long been shaped by a crime control rather than a harm reduction imperative. Consequently, police officers’ responses to safe consumption sites (SCSs), where people who use illicit drugs can reduce personal health risks by administering previously obtained drugs in the presence of trained staff, were initially hostile. This paper draws on interview data from police officers in two western Canadian cities to highlight an apparent softening in attitudes, perhaps due to the current fentanyl-driven drug poisoning crisis. While some officers clearly recognized their public health benefits, others accepted SCSs, acknowledging the futility of a continued ‘war on drugs’. Some voiced reservations about SCSs, but not because of a generic ‘drugs are bad’ sentiment. Rather, they worried about specific downstream implications for communities and police work. These findings, reflecting apparent changes in police officers’ responses to SCSs, are discussed in the context of contemporary debates about police culture and the possibilities and desirability of pursuing police reform.